Temperature and thickness dependence of tunneling anisotropic magnetoresistance in exchange-biased Py/IrMn/MgO/Ta stacks - Reichlová, H.; Novák, V.; Kurosaki, Y.; Yamada, M.; Yamamoto, H.; Nishide, A.; Hayakawa, J.; Takahashi, H.; Marysko, M.; Wunderlich, J.; Marti, X.; Jungwirth, T. (IOP Publishing, 2016)
Weinvestigate the thickness and temperature dependence of a series of Ni0.8Fe0.2/Ir0.2Mn0.8 bilayer samples with varying thickness ratio of the ferromagnet/antiferromagnet (tFM tAFM) in order to explore the exchange coupling strengths in tunneling anisotropic magnetoresistance (TAMR) devices. Specific values of tFM tAFM lead to four distinct scenarios with specific electric responses to moderate magnetic fields. The characteristic dependence of the measured TAMR signal on applied voltage allows us to confirm its persistence up to room temperature despite an overlapped contribution by a thermal magnetic noise.